Penegakan Hukum Terhadap Jual Beli Pakaian Bekas Impor â€œThriftingâ€ Di Wilayah Banyumas - Yulianti, Tri; Marlia Hafny Afrilies; Maya Ruhtianti (JURNAL PENELITIAN SERAMBI HUKUM, 2024)
This study examines the buying and selling of imported used clothing in the Banyumas area which aims to identify and analyze law enforcement against the buying and selling of imported used clothing in the Banyumas area, and to identify and analyze the obstacles to law enforcement against the buying and selling of imported used clothing "thrifting" in the Banyumas area. This type of research uses empirical legal research, with the nature of descriptive research. The research location is at the Satria Sports Arena (GOR) Sunday Market, Purwokerto. Types and sources of data in research consists of two types, primary data and secondary data. Data collection techniques are by observation, interviews, and literature studies. Qualitative data analysis techniques. The results of this study are that law enforcement against the buying and selling of imported used clothing in the Banyumas area has not been carried out optimally, this can be proven by the absence of law enforcement carried out by the Department of Trade and Industry in the Banyumas area against traders of imported used clothing. Obstacles to law enforcement against thrifting buying and selling of imported used clothing in the Banyumas area is the lack of awareness of traders and consumers to comply with a statutory regulation.